Modeling and simulation of the sub carrier multiplexed radio over fiber system - Mahyuddin Arsat, 1983-, author; Sevia Mahdaliza Idrus Sutan Nameh, author; The 5th Student Conference on Research and Development (SCOReD 2007) (2007: Selangor) (Skudai : Universiti Teknologi Malaysia, 2007)
PRZSL